The Perbedaan hasil belajar matematika siswa menggunakan metode pembelajaran blendid learning berbantuan google classroom dan metode pembelajaran langsung pada materi lingkaran di SMA Negeri 3 Manado - Khagow, Sisilia Ruth; Pitoy, Cori; Kaunang, Derel Filandy (De Fermat : Jurnal Pendidikan Matematika, 2026)
This study aims to determine the differences in student learning outcomes between those taught using a blended learning method supported by Google Classroom and those taught using a face-to-face method on the topic of circles at Manado State High School 3. This study employs a quantitative approach using a quasi-experimental design and a post-test only control design. The research sample consisted of two classes: Class XI A as the experimental class and Class XI B as the control class. Data collection utilized a post-test to measure learning outcomes. Data were analyzed using normality tests, homogeneity tests, and t-tests. The results indicated that the average learning outcome for students in the experimental class was 80.97, while that for the control class was 75.18. The results of the hypothesis test yielded a calculated t-value of 1.905 and a critical t-value of 1.672 at a significance level of 0.05, so the calculated t-value was greater than the critical t-value. Thus, there was a difference in student learning outcomes, with students taught using blended learning supported by Google Classroom achieving better results than those taught using the direct instruction method.